Survival trends of patients with non‐metastatic gastric adenocarcinoma in the US and European countries: the impact of decreasing resection rates - Lei Huang; Lina Jansen; Rob H.A. Verhoeven; Jelle P. Ruurda; Liesbet Van Eycken; Harlinde De Schutter; Jan Johansson; Mats Lindblad; Tom B. Johannesen; Vesna Zadnik; Tina Žagar; Sjoerd M. Lagarde; et al. (Cancer Communications, 2022)
Abstract Background We previously observed decreasing resection rates of non‐metastatic gastric adenocarcinoma (GaC) in the US and some European countries. If and to what extent these trends affect the trends in overall survival (OS) of patients with non‐metastatic GaC at the population level remain unclear. This large international population‐based cohort study aimed to assess the impact of the previously observed decreasing resection rates on multivariable‐adjusted trends in the long‐term OS of patients with non‐metastatic GaC. Methods Individual‐level data of patients with non‐metastatic GaC were obtained from the national cancer registries of the Netherlands, Belgium, Sweden, Norway, and Slovenia, and the US Surveillance, Epidemiology, and End Results database. We analyzed data for each country separately. Associations between year of diagnosis and OS were assessed using Cox proportional hazards regression model with adjustment for multiple prognostic variables, with and without including resection and chemotherapy as potential explanatory variables. Results A total of 66,398 non‐metastatic GaC patients diagnosed in 2003‐2016 were analyzed, with an accumulated follow‐up of 172,357 person‐years. Without adjustment for resection, OS was improved only slightly in the US [hazard ratio (HR)per year = 0.99; HR≥ vs. <2010 = 0.96], and no improvement was observed in the investigated European countries, with OS even worsening in Sweden (HRper year = 1.03; HR≥ vs. <2010 = 1.17). After adjusting for resection, the increasing OS trend became stronger in the US (HRper year = 0.98; HR≥ vs. <2010 = 0.88), and the temporal trend became insignificant in Sweden. In Slovenia (HRper year = 0.99; HR≥ vs. <2010 = 0.92) and Norway (HRper year = 0.97; HR≥ vs. <2010 = 0.86), improved OS over time emerged after resection adjustment. Improved OS in patients undergoing resection was observed in the US, the Netherlands, and Norway. Adjustment for chemotherapy did not alter the observed associations. Stratified analyses by tumor location showed mostly similar results with the findings in all patients with non‐metastatic GaCs regarding the associations between year of diagnosis and survival. Conclusions OS of patients with non‐metastatic GaC mostly did not improve in selected European countries and was even worsened in Sweden, while it was slightly increased in the US in the early 21st century. Progress in OS of patients with non‐metastatic GaC seems to have been impeded to a large extent by decreasing rates of resection.